Project finance principles & applications - Thornham, Roger; Sullivan, Colin (London : Financial i Production, 1993)
This video consists of two videos. Part one described the principles of Project Finance ; Part two described the applications of Project Finance
Two videos in one container + three books of training guide
Produced in association with Babcock & Brown
Copy available in DVD format
Writer, Warren F. Smith
Keywords: Capital investments; Corporations -- Finance